Morbidity and mortality Post laparoscopic Cholecystectomy in cirrhotic patients - Al. Zobaidy, Hayder (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Cholecystectomy in cirrhotic patients is commonly followed by high morbidity and mortality, the incidence of hepatic cirrhosis has increased since last decade as well as the occurrence of complication such as liver failure, portal hypertension, and biliary disorders. Patients and methods: laparoscopic Cholecystectomy was performed in 24 cirrhotic patients (18 child A and 6 child B) in an effort to obtain lower complications and mortality rates. The mean age of the group was 51.8 years, ten of the 24 patients were men and 14 female. Results: intraoperative complications such as bleeding, dense adhesion and long operative time were recorded. Conclusion: laparoscopic Cholecystectomy was safe and will tolerated by selected cirrhotic patients (child A and B) with clear indication for surgery.